Urea azines (bisguanidines): electronic structure, redox properties, and coordination chemistry - Herrmann, Hendrik Hans; Reinmuth, Matthias; Wiesner, Sven; Hübner, Olaf; Kaifer, Elisabeth; Wadepohl, Hubert; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2015)
Abstract Urea azines are a largely neglected class of compounds. We show herein that they can easily be synthesized and sublimed at higher temperatures (90?100 °C) without decomposition. Our discussion includes the derivatives N,N?-diisopropylurea azine (2), tetramethylurea azine (3), and N,N?-dimethylethyleneurea azine (4) as examples. Vibrational spectroscopy and quantum chemical calculations were used to study their electronic structure in detail. A clear trend in the calculated decomposition to N2 and carbene is found, but the analysis reveals that this trend reflects the stability of the carbene decomposition product rather than changes in the electronic structure of the urea azines. Using cyclic voltammetry (CV) measurements we show that the urea azines are strong organic electron donors, which can be oxidized reversibly in two well-separated one-electron steps. The radical salt 4(TCNQ), featuring radical monocations and radical monoanions, which form mixed stacks in the solid state, was prepared by reaction of neutral 4 with tetracyanoquinodimethane (TCNQ). Oxidation of 4 with silver salts Ag+X? (X = BF4 or PF6) was accompanied by dehydrogenation, leading to intensively red-brown colored radical azoimidazolium dyes. Furthermore, urea azines were used as chelating ligands. In the case of 2, coordination to late transition metals initiates tautomerization. Reaction of 2 with boron hydrides leads to hydrogen elimination and formation of new B,N bi-heterocyclic ring structures.
Gesehen am 27.08.2020